2007
DOI: 10.1186/1748-5908-2-8
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties implementing a mental health guideline: an exploratory investigation using psychological theory

Abstract: Background: Evaluations of interventions to improve implementation of guidelines have failed to produce a clear pattern of results favouring a particular method. While implementation depends on clinicians and managers changing a variety of behaviours, psychological theories of behaviour and behaviour change are seldom used to try to understand difficulties in implementation or to develop interventions to overcome them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
140
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(146 citation statements)
references
References 20 publications
5
140
0
1
Order By: Relevance
“…In the current economic context, further investment in clinical psychologists seems unlikely, but a greater focus on training and supervising nurses and other staff to deliver psychological interventions has been shown to be possible in some psychosis services, 55 although problems with sustainability have also been identified. 56,57 This might include so-called 'low-intensity' psychological interventions that, although lacking a strong evidence base, may be easier for service users with complex mental health problems to engage with and assist with addressing some of the comorbidities and other issues that impede progress towards successful community discharge (e.g. anxiety management, relapse prevention, motivational interviewing).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current economic context, further investment in clinical psychologists seems unlikely, but a greater focus on training and supervising nurses and other staff to deliver psychological interventions has been shown to be possible in some psychosis services, 55 although problems with sustainability have also been identified. 56,57 This might include so-called 'low-intensity' psychological interventions that, although lacking a strong evidence base, may be easier for service users with complex mental health problems to engage with and assist with addressing some of the comorbidities and other issues that impede progress towards successful community discharge (e.g. anxiety management, relapse prevention, motivational interviewing).…”
Section: Discussionmentioning
confidence: 99%
“…Discharged from the rehabilitation unit 219 (66) Ready to be discharged from the rehabilitation unit 48 (14) Discharged or ready to be discharged from the rehabilitation unit 267 (80) Successfully discharged from the rehabilitation unit 187 (56) Successfully discharged or ready to be discharged from the rehabilitation unit 235 (71) The results of the further multivariable exploratory analyses are shown in Tables 25 and 26. Table 25 shows the variables associated with successful discharge at the 12-month follow-up.…”
Section: -Month Follow-up N (%)mentioning
confidence: 99%
“…However, reviews (e.g., Campbell et al, 2015;Pavey et al, 2011) have reported the schemes to be no more effective than usual care. Pavey and colleagues identified the importance of theory in furthering our understanding of the effectiveness of ERS as causal relationships can be uncovered, providing implications for interventions (Michie et al, 2007). Such theory-based research in ERS may provide insight into the adoption and maintenance of physical activity (Baranowski & Jago, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Questi nostri risultati sono in linea con un recente studio [9] che indica nelle risorse "tempo" e "training" i due principali problemi nella implementazione delle LLGG, all'interno del dominio "contesto ambientale e risorse".…”
unclassified